2017
DOI: 10.1016/j.juro.2017.03.132
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Whole Body Pain in Urological Chronic Pelvic Pain Syndrome at Baseline: A MAPP Research Network Study

Abstract: Purpose We characterized the location and spatial distribution of whole body pain among patients with urologic chronic pelvic pain syndrome (UCPPS) using a body map; and compared the severity of urinary symptoms, pelvic pain, non-pelvic pain, and psychosocial health among patients with different pain patterns. Methods 233 women and 191 men with UCPPS enrolled in a multi-center, one-year observational study completed a battery of baseline measures, including a body map describing the location of pain during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
111
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 28 publications
9
111
3
Order By: Relevance
“…Our novel observation of two flare patterns, one with and one without concomitant increases in extrapelvic pain, is consistent with the broader hypothesis of the existence of at least two distinct UCPPS phenotypes . Moreover, it also suggests that the pathologies underlying these two phenotypes may contribute to flare pathology.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our novel observation of two flare patterns, one with and one without concomitant increases in extrapelvic pain, is consistent with the broader hypothesis of the existence of at least two distinct UCPPS phenotypes . Moreover, it also suggests that the pathologies underlying these two phenotypes may contribute to flare pathology.…”
Section: Discussionsupporting
confidence: 88%
“…Whole body pain was investigated by asking participants to mark areas where they felt “pain or discomfort” that day and to indicate their average level of pain in each marked area (scale = 0‐10) on two whole body maps (front and back) modified from the Brief Pain Inventory (BPI; Figure A1). Similar to previous MAPP analyses, we grouped the 42 extrapelvic areas (all areas except for 14‐16) into the following seven regions: back, head, right leg, left leg, right arm, left arm, and trunk . For pelvic and genital pain, participants reported their average levels of pain or discomfort in six (male) or seven (female) pelvic/genital areas (scale = 0‐10), using sex‐appropriate diagrams modified from the BPI (Figure A2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently more studies are needed to identify if there are unique affective characteristics that differentiate COPCs (and by implication CS) from other forms of chronic pain. As mentioned previously, the study of UCPPS patients demonstrated that greater wide-spreadedness of pain was associated with worse depressive and anxiety symptoms (as measured by the HADS) and worse mental health overall (as measured by the SF12) for both males and females (Lai et al, 2017). …”
Section: Chronic Overlapping Pain Conditions (Copcs): the Diagnosmentioning
confidence: 59%
“…In this study, 75% reported pain beyond the pelvic region, with 38% reporting pain in more than 3 sites simultaneously. Those with broader pain distributions demonstrated significantly poorer scores on the other elements of the SPACE symptom cluster (Lai et al, 2017). Similar findings have been reported in the context of TMD (Slade et al, 2013) and FM (Cassisi et al, 2014).…”
Section: Chronic Overlapping Pain Conditions (Copcs): the Diagnosmentioning
confidence: 99%